Accounting undergraduates learning approaches: case of a Malaysian public university - Lau, Yeng Wai; Lim, Shi Yee (Universiti Putra Malaysia Press, 2015)
Concerns about graduates’ employability are not new. Being burdened with accounting standards to be memorised and regurgitated in examinations does little to encourage learning with understanding, i.e. deep learning. Yet, deep learning is pertinent for development of generic employability skills such as problem solving and critical thinking. This study examines the extent to which accounting undergraduates at a public university in Malaysia adopt deep learning via a questionnaire survey. Results suggest that surface learning, which promotes rote memorisation and is often blamed for graduates’ incompetence, is the first step towards deep learning. Having a thirst for meanings has been found to be pertinent to motivate undergraduates to move from rote memorisation to seek meanings and thus deep learning. Female undergraduates have been found to be more inclined to adopt deep learning compared with their male counterparts. Nonetheless, much is still to be learned to promote deep learning, which is a complex process that is not constrained to the campus.